Penentuan kandungan antioksidan dan fenolik total dari 5 spesies tumbuhan Famili Myrtaceae - Yefrida; Isra, Hayatul; Refilda (Jurnal Kimia Unand, 2023)
Plants that come from the Myrtaceae family are plants that are found in the tropics. These plants are widely used by the community as spices or medicinal ingredients. The research conducted aims to determine the antioxidant content and total phenolic content of 5 types of leaves of this plant. The total antioxidant content was determined using the MPM (Modified Phenanthroline Method) method while the total phenolic content was determined using the Folin-Ciocalteau method. Based on the research that has been done, it is found that the largest antioxidant content is found in the leaves of the Syzigium malaccence) plant 122.73 ± 3.10 mg AA/g DW while the largest total phenolic content is found in the leaves of the plant (Psidium guajava) 58.84 ± 1.86 mg GAE/g DW.